Kyai Leadership in Internalizing Nationalism Values at Pesantren - Apud Apud; Hj Sammali bin Hj Adam; Ferdiansyah Irawan (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2020)
This study aims to examine the leadership of the kyai in Pesantren Salâfiyah Cidahu Pandeglang. It specifically explored the leadership of the kyai and its role in internalizing nationalism values for students in pesantren. This study used a descriptive-qualitative method. The data were obtained through interviews, observation and documentation. The results showed that the leadership of the kyai has played a role in internalizing a spirit of nationalism for the students. The process of internalizing the spirit of nationalism was carried out through giving advice and exemplary, book recitation activities, baḥṡ al-masâ'il, community service, entrepreneurial activities, organizational activities, leadership training, maintaining traditions, and democracy-related activities. Lack of the students' motivation to learn and the limited facilities and infrastructure were the obstacles in nurturing the values of nationalism. To solve the obstacles, kyai provided motivation for the students, built the students' confidence and self-confidence, and established network with the society and government.